Neck masses due to internal jugular vein phlebectasia: Frequency in Menkes disease and literature review of 85 pediatric subjects. Issue 6 (15th April 2020) - Stevens, Kristen E.; Price, Julienne E.; Marko, Jamie; Kaler, Stephen G.
Abstract: Classic Menkes disease is a rare X‐linked recessive disorder of copper metabolism caused by pathogenic variants in the copper transporter gene, ATP7A . Untreated affected individuals suffer failure to thrive and neurodevelopmental delays that begin at 6–8 weeks of age and progress inexorably to death, often within 3 years. Subcutaneous injections of Copper Histidinate (US Food and Drug Administration IND #34, 166, Orphan product designation #12‐3663) are associated with improved survival and neurological outcomes, especially when commenced within a month of birth. We previously identified internal jugular vein phlebectasia (IJP) in four Menkes disease subjects. This feature and other connective tissue abnormalities appear to be consequences of deficient activity of lysyl oxidase, a copper‐dependent enzyme. Here, we report results from a prospective study of IJP based on 178 neck ultrasounds in 66 Menkes subjects obtained between November 2007 and March 2018. Nine patients met the criterion for IJP (one or more cross‐sectional area measurements exceeding 2.2 cm 2 ) and five subjects had clinically apparent neck masses that enlarged over time. Our prospective results suggest that IJP occurs in approximately 14% (9/66) of Menkes disease patients and appears to be clinically benign with no specific medical or surgical actionability. We surveyed the medical literature for prior reports of IJP in pediatric subjects and identified 85 individuals and reviewed the distribution of this abnormality by gender, sidedness, and underlying etiology. Taken together, Menkes disease accounts for 16% (15/94) of all reported IJP individuals. Neck masses from IJP represent underappreciated abnormalities in Menkes disease.